The Benefits of Infrared Therapy, Mirror Exercise, and Faradic Current in a Patient with Bell’s Palsy: Case Study - Rachmawati, Dhyan; -, Sugiono; Nugroho, Fendy; -, Noerdjanah (Jurnal Fisioterapi Terapan Indonesia, 2025)
Background: Bell’s Palsy is defined as paralysis of one side of the facial nerve, with an unknown cause. Several other conditions can also cause facial paralysis, such as brain tumors, stroke, myasthenia gravis, and Lyme disease. However, if no specific cause can be identified, this condition is known as Bell’s Palsy, which is caused by swelling and pressure on the nerve at the stylomastoid foramen, leading to nerve compression or damage. Often, the affected side’s eye cannot be closed. Physiotherapy management plays a vital role in the rehabilitation process for Bell’s Palsy patients to reduce symptoms, accelerate recovery, and restore facial muscle function. This study aims to determine the effectiveness of infrared modality, mirror exercises, and faradic current in patients with Bell’s Palsy. Objectives: To examine physiotherapy management using Infrared, Mirror Exercise, and Faradic Current in cases of Bell’s Palsy. Methods: The method involved patients with left-sided Bell’s Palsy. Assessments were conducted using Manual Muscle Testing (MMT) to evaluate facial muscle strength and the Ugok Fish test to assess the functional ability of facial muscles. The therapy was administered four times with a combination of infrared, mirror exercises, and faradic current. Results: Evaluation of facial muscle strength on the left side using MMT showed that the frontalis muscle score increased from 1 at T1 to 3 at T4, and the orbicularis oris muscle score increased from 1 at T1 to 3 at T4 on the affected side. Additionally, functional ability measured by the Ugok Fish test improved from 50% initially to 60%. Conclusion: The administration of infrared, mirror exercises, and faradic current therapy resulted in increased muscle strength and improved functional activity in a case of Bell’s Palsy.